Analysis of the effectiveness of bus lane with intermittent priority - Szarata, Mateusz; Olszewski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper compares benefits of bus lanes with intermittent priority to standard bus lanes. The study was based on traffic models made by using HCM 2010 method and microsimulation models developed with PTV Vissim software. The paper also presents operating principles of bus lane with intermittent priority and the results of traffic surveys conducted in Rzeszow. The analysis shows that when compared to the standard bus lane, the use of bus lane with intermittent priority can bring benefits for streets with lower bus flows.